Epinephrine in out-of-hospital cardiac arrest: A critical review - Reardon, Peter M. (Second Affiliated Hospital of Zhejiang University School of Medicine, 2013)
BACKGROUND: Epinephrine is recommended in advanced cardiac life support guidelines for use in adult cardiac arrest, and has been used in cardiopulmonary resuscitation since 1896. Yet, despite its long time use and incorporation into guidelines, epinephrine suffers from a paucity of evidence regarding its influence on survival. This critical review was conducted to address the knowledge deficit regarding epinephrine in out-of-hospital cardiac arrest and its effect on return of spontaneous circulation, survival to hospital discharge, and neurological performance. METHODS: The EMBASE and MEDLINE (through the Pubmed interface) databases, and the Cochrane library were searched with the key words “epinephrine”, “cardiac arrest” and variations of these terms. Original research studies concerning epinephrine use in adult, out-of-hospital cardiac arrest were selected for further review. RESULTS: The search yielded nine eligible studies based on inclusion criteria. This includes five prospective cohort studies, one retrospective cohort study, one survival analysis, one case control study, and one RCT. The evidence clearly establishes an association between epinephrine and increased return of spontaneous circulation, the data were conflicting concerning survival to hospital discharge and neurological outcome. CONCLUSIONS: The results of this review exhibit the paucity of evidence regarding the use of epinephrine in out of hospital cardiac arrest. There is currently insufficient evidence to support or reject its administration during resuscitation. Larger sample, placebo controlled, double blind, randomized control trials need to be performed to definitively establish the effect of epinephrine on both survival to hospital discharge and the neurological outcomes of treated patients.